Hydroelectric Energy: Sustainable and Economical Solutions for Water Systems. Issue 12 (29th November 2018) - Morgan, Nicholas; Kirven, Kelly; Parker, Michael
Abstract : Water utilities might want to consider using hydroelectric power to compensate for increased infrastructure costs and financial shortfalls resulting from decreased demand.